Tanda dan Gejala pada Kehamilan dengan Preeklampsia di Wilayah Pertanian Jember - Dini Kurniawati; Adilah Mia Azubah; Eka Afdi Septiyono; Iis Rahmawati; Lantin Sulistyorini (Yayasan Literasi Sains Indonesia, 2023)
Preeclampsia is a complication problem that occurs in pregnant women with gestational age above 20 weeks with hypertension and proteinuria. The relatively high maternal mortality rate (MMR) is one of the problems that must be faced at this time, considering that the problem of preeclampsia is one of the main causes of morbidity, maternal and perinatal mortality in the world. The purpose of this study is as a preventive measure to prevent further eclampsia from occurring in preeclamptic women in the Jember Agricultural Area. The research design used descriptive analytic with a cross sectional approach. This research was conducted on 150 pregnant women who had preeclampsia using the Quota Sampling technique. Data collection used a questionnaire about the signs and symptoms of preeclampsia and the book for pregnant women with preeclampsia in December 2022-January 2023. The results showed that the majority of respondents had signs of high blood pressure (80.7%) and some were not accompanied by the presence of proteinuria (55.3%). Most pregnant women with preeclampsia had mild symptoms, namely sometimes feeling dizzy (53.3%) and all body aches (48.0%) in the working area of the Banjarsengon Health Center, Panti Health Center and Tempurejo Health Center. The discussion of this study illustrates that the signs and symptoms of pregnant women with preeclampsia have high blood pressure accompanied by symptoms of feeling dizzy.